Boron-doped graphene composite solid electrolyte and preparation and application thereof
By using electrospinning technology to prepare boron-doped graphene composite materials in solid electrolytes, the check and balance problems between the conductivity of solid electrolytes and the number of lithium ions in the prior art are solved, and the efficient rate performance and cycle of lithium batteries are achieved stability.
Patent Information
- Application Number
- CN202411469274.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-21
AI Technical Summary
There is a check and balance relationship between the ion conductivity and the number of lithium ion migrations in the existing solid electrolytes, which is difficult to optimize at the same time. The physical properties are easy to volatile, flammable and have poor mechanical strength, which cannot effectively solve the short circuit problem caused by lithium dendrites' growth.
Electrospinning technology is used to prepare boron-doped graphene composite solid electrolyte. By combining boron-doped graphene as a filler with polyoxyethylene matrix, a composite solid electrolyte is formed, and its electrochemical performance is optimized.
The ion conductivity and lithium ion migration number of the composite solid electrolyte are significantly improved, breaking the checks and balance relationship in the original technology, and giving lithium batteries good rate performance and cycle stability.
Smart Images

Figure CN119315099A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a technology in the field of lithium batteries, specifically a boron-doped graphene composite solid electrolyte and its preparation and application. Background Art
[0002] Existing solid electrolytes often use polyethylene oxide (PEO) as the matrix material, but its low ionic conductivity and lithium ion transference number limit its practical application. Currently, anions are often covalently linked to increase the lithium ion transference number, but the ionic conductivity will be reduced. There is a balance between the two, and it is difficult to optimize them at the same time. Summary of the invention
[0003] In view of the shortcomings of the prior art that it is difficult to simultaneously optimize the ionic conductivity and lithium ion migration number of PEO solid electrolytes, and the physical properties of the existing electrolytes are volatile, flammable and have poor mechanical strength, and cannot solve the short-circuit problem caused by the growth of lithium dendrites, the present invention proposes a boron-doped graphene composite solid electrolyte and its preparation and application. The prepared composite solid electrolyte has high ionic conductivity and lithium ion migration number, and gives the lithium battery good rate performance and cycle stability.
[0004] The present invention is achieved through the following technical solutions:
[0005] The invention relates to a method for preparing a boron-doped graphene composite solid electrolyte. The method comprises the following steps: preparing a PAN porous film from a mixed solution of polyacrylonitrile (PAN) and N,N-dimethylformamide by an electrostatic spinning technology; mixing boron-doped graphene, polyethylene oxide, lithium bis(trifluoromethanesulfonyl imide) and acetonitrile to prepare a PEO casting solution, and then casting the solution on the PAN porous film. After vacuum drying, a composite solid electrolyte is formed which uses polyacrylonitrile fiber as a support, polyethylene oxide as a matrix and boron-doped graphene as a filler.
[0006] The usage ratio of polyacrylonitrile and N,N-dimethylformamide is 1g:1mL.
[0007] The boron-doped graphene is prepared by mixing graphene oxide and boric acid and subjecting them to an annealing reaction, wherein the mass ratio of graphene oxide to boric acid is preferably 1:2-1:8.
[0008] The amount of the boron-doped graphene preferably accounts for 1%-5% of the mass of polyethylene oxide, and the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to polyethylene oxide is preferably 1:3-1:1.
[0009] The usage ratio of the polyethylene oxide and acetonitrile is 0.5465 g:12 mL.
[0010] The annealing reaction temperature is preferably 700°C-900°C.
[0011] The annealing reaction is preferably carried out under an argon atmosphere.
[0012] The electrospinning method used a syringe to inject the PAN spinning solution into a stainless steel needle, and used aluminum foil as a receiving matrix. The distance between the needle and the receiving matrix was set to 15 cm, and the pushing speed was adjusted to 1 μm s -1 , a voltage of 15 kV was applied for electrospinning.
[0013] The invention relates to a boron-doped graphene composite solid electrolyte prepared by the above method, comprising: polyacrylonitrile fibers as a composite solid electrolyte support, polyethylene oxide and lithium bis(trifluoromethanesulfonyl imide) as a matrix, and boron-doped graphene with electron-deficient boron-containing groups as a filler, wherein: the supporting fibers are interwoven in the composite solid electrolyte to form a three-dimensional skeleton, the matrix forms a continuous lithium ion transmission phase in the composite solid electrolyte, and the filler is uniformly dispersed inside the polymer matrix to adsorb anions and reduce the crystallinity of the matrix.
[0014] The diameter of the boron-doped graphene is 500nm-3μm.
[0015] The diameter of the polyacrylonitrile fiber is 300nm-400nm.
[0016] The present invention relates to the application of the boron-doped graphene composite solid electrolyte, which is assembled into stainless steel|composite solid electrolyte|stainless steel battery, lithium|composite solid electrolyte|lithium battery and lithium iron phosphate|composite solid electrolyte|lithium battery.
[0017] The lithium-ion battery is preferably assembled in a glove box filled with high-purity argon.
[0018] The stainless steel|composite solid electrolyte|stainless steel battery is obtained by sequentially placing a composite solid electrolyte and a stainless steel sheet in a battery shell and assembling them. The stainless steel|composite solid electrolyte|stainless steel battery is tested for its electrochemical impedance spectrum at an amplitude of 10mV and a frequency range of 100k-0.1Hz by an electrochemical workstation to obtain the ionic conductivity of the composite solid electrolyte.
[0019] The lithium|composite solid electrolyte|lithium battery is obtained by sequentially placing a lithium sheet, a composite solid electrolyte, and a lithium sheet in a battery shell and assembling them. The lithium|composite solid electrolyte|lithium battery is tested by an electrochemical workstation for the current-time curve of the battery at a polarization voltage of 10mV and a polarization time of 3600s and the electrochemical impedance spectrum before and after polarization to obtain the lithium ion migration number of the composite solid electrolyte. In addition, the lithium|composite solid electrolyte|lithium battery is tested for lithium stripping / deposition cycles at different current densities by a battery testing system to obtain the critical current density of the composite solid electrolyte.
[0020] The lithium iron phosphate|composite solid electrolyte|lithium battery is obtained by sequentially placing a lithium iron phosphate pole piece, a composite solid electrolyte, and a lithium sheet in a battery shell and assembling them. The lithium iron phosphate|composite solid electrolyte|lithium battery is tested for rate performance and cycle stability by cycling 10 times at 0.1C, 0.2C, and 0.5C rates and 400 times at 0.3C rate through a battery testing system. Technical Effects
[0021] The present invention dopes boron atoms into graphene through solid phase reaction, and applies boron-doped graphene as filler to PEO solid electrolyte to optimize the electrochemical performance of solid electrolyte. Compared with the prior art, the present invention simultaneously optimizes the ionic conductivity and lithium ion migration number of the boron-doped graphene composite solid electrolyte, breaking the balance between the two in the original PEO solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the boron-doped graphene composite solid electrolyte prepared in Example 1;
[0023] Figure 2 Electrochemical impedance spectra of the stainless steel|composite solid electrolyte|stainless steel battery assembled in Example 1 at room temperature and current-time curve of the lithium|composite solid electrolyte|lithium battery at room temperature, and electrochemical impedance spectra before and after polarization;
[0024] Figure 3 The lithium stripping / deposition cycle diagram of the lithium|composite solid electrolyte|lithium battery assembled in Example 1 at different current densities at room temperature;
[0025] Figure 4 This is a rate performance diagram of the lithium iron phosphate | composite solid electrolyte | lithium battery assembled in Example 1 at room temperature;
[0026] Figure 5 This is the cycling stability diagram of the lithium iron phosphate | composite solid electrolyte | lithium battery assembled in Example 1 at room temperature. DETAILED DESCRIPTION Example 1
[0027] This embodiment includes the following steps:
[0028] Step 1. Weigh 250 mg of graphene oxide and 1250 mg of boric acid into a conical flask, then add 50 mL of deionized water, and obtain a uniform liquid after sufficient magnetic stirring and ultrasonic treatment. The liquid is then freeze-dried and the product is placed in a tubular furnace for annealing reaction at 900° C. for 3 hours in an argon atmosphere. After centrifugal washing 4 times in deionized water, boron-doped graphene is obtained.
[0029] Step 2: Weigh 0.0164 g of boron-doped graphene, 0.5465 g of polyethylene oxide, and 0.3644 g of lithium bis(trifluoromethanesulfonyl)imide into a conical flask, then add 12 mL of acetonitrile, and stir magnetically at room temperature for 12 h to obtain a uniform PEO casting solution; separately weigh 0.7 g of polyacrylonitrile and 7 mL of N,N-dimethylformamide into a conical flask, and stir magnetically at room temperature for 6 h to obtain a uniform PAN spinning solution.
[0030] Step 3: Cover the stainless steel roller of the electrospinning machine with a layer of aluminum foil as the receiving substrate of the PAN porous film, transfer the PAN spinning solution prepared in step 2 into a 20 mL syringe and fix it, and set the pushing speed to 1 μm s. -1 , adjust the distance between the needle and the receiving substrate to 15 cm, apply a high voltage of 15 kV between the needle and the receiving substrate, and after about 6 hours, remove the aluminum foil with the electrospun film and transfer it to a vacuum drying oven and dry it at 60°C for 12 hours to obtain a PAN porous film.
[0031] Step 4: remove the aluminum foil on the PAN porous film, cast the PEO casting solution prepared in step 2 on both sides of the PAN porous film, transfer it to a fume hood and let it stand for two days to evaporate the acetonitrile solvent, then transfer it to a vacuum drying oven and dry it at 60°C for 12 hours to remove the residual acetonitrile solvent to obtain a boron-doped graphene composite solid electrolyte.
[0032] Step 5. Cut the boron-doped graphene composite solid electrolyte into discs with a diameter of 19 mm, and assemble them into stainless steel | composite solid electrolyte | stainless steel battery, lithium | composite solid electrolyte | lithium battery and lithium iron phosphate | composite solid electrolyte | lithium battery to test the ionic conductivity, lithium ion migration number, critical current density of the boron-doped graphene composite solid electrolyte and the rate performance and cycle stability of the lithium iron phosphate | composite solid electrolyte | lithium battery.
[0033] like Figure 1 As shown, the boron-doped graphene is evenly dispersed in the matrix of the composite solid electrolyte in the form of particles with a particle size of 500nm-3μm. Its uniform distribution can reduce the crystallinity of polyethylene oxide, and through the electron-deficient boron-containing groups on it, it interacts with the anions in the lithium salt through Lewis acid-base interactions, restrains the movement of anions, releases more free lithium ions, and improves the ionic conductivity and lithium ion migration number of the composite solid electrolyte. The thickness of the boron-doped graphene composite solid electrolyte is about 200μm.
[0034] like Figure 2 As shown in Figure 2, it is calculated that the ionic conductivity of the boron-doped graphene composite solid electrolyte at room temperature is 9.27×10 -5 S cm-1 , the lithium ion migration number is 0.57.
[0035] like Figure 3 As shown in Figure 2, the critical current density of the boron-doped graphene composite solid electrolyte exceeds 0.05 mA cm -2 , the overpotential is stable at around 0.12V.
[0036] like Figure 4 As shown in Figure 2, at room temperature, the capacities of the lithium iron phosphate|composite solid electrolyte|lithium battery assembled with boron-doped graphene composite solid electrolyte at 0.1C and 0.2C rates are approximately 160 and 151 mAh g, respectively. -1 , stable charge-discharge cycle can be achieved at 0.5C rate, with a capacity of about 138mAh g –1 .
[0037] like Figure 5 As shown in Figure 2, under room temperature conditions, the discharge capacity of the lithium iron phosphate|composite solid electrolyte|lithium battery assembled with boron-doped graphene composite solid electrolyte at a rate of 0.3C is 149.3 mAh g -1 After 400 cycles, the capacity can still be maintained at 89.7% of the initial capacity.
[0038] In summary, the boron-doped graphene composite electrolyte prepared in this embodiment has excellent electrochemical properties. Example 2
[0039] This embodiment includes the following steps:
[0040] Step 1. Weigh 250 mg of graphene oxide and 500 mg of boric acid into a conical flask, then add 50 mL of deionized water, and obtain a uniform liquid after sufficient magnetic stirring and ultrasonic treatment. The liquid is then freeze-dried and the product is placed in a tubular furnace for annealing reaction at 700° C. for 3 hours in an argon atmosphere. After centrifugal washing 4 times in deionized water, boron-doped graphene is obtained.
[0041] Step 2: Weigh 0.0546 g of boron-doped graphene, 0.5465 g of polyethylene oxide, and 0.3644 g of lithium bis(trifluoromethanesulfonyl)imide into a conical flask, then add 12 mL of acetonitrile, and stir magnetically for 12 h at room temperature to obtain a uniform PEO casting solution; in addition, prepare a PAN spinning solution according to the method of step 2 of Example 1.
[0042] Step 3: Prepare a PAN porous film according to the method of step 3 of Example 1.
[0043] Step 4: Prepare a boron-doped graphene composite solid electrolyte according to the method of step 4 of Example 1.
[0044] Step 5, testing of ionic conductivity, lithium ion migration number and critical current density of boron-doped graphene composite solid electrolyte and testing of rate performance and cycle stability of lithium iron phosphate | composite solid electrolyte | lithium battery: The assembly and testing methods are the same as step 5 of Example 1. The ionic conductivity of the boron-doped graphene composite solid electrolyte is calculated to be 2.76×10 -5 S cm -2 , the lithium ion transfer number is 0.32. The critical current density of the boron-doped graphene composite solid electrolyte is only 0.02 mA cm -2 , and the overpotential exceeds 0.15 V. The lithium iron phosphate|composite solid electrolyte|lithium battery assembled with boron-doped graphene composite solid electrolyte has a specific capacity of 143 mAh g at a rate of 0.1C. -1 The specific capacity at 0.5C rate is 73 mAh g -1 , which is about half of the specific capacity at 0.1C rate. When cycled at 0.3C rate, the specific capacity is 108 mAh g -1 After 150 cycles, the specific capacity is 81 mAh g -1 . Example 3
[0045] This embodiment includes the following steps:
[0046] Step 1. Weigh 250 mg of graphene oxide and 2000 mg of boric acid into a conical flask, then add 50 mL of deionized water, obtain a uniform liquid after sufficient magnetic stirring and ultrasonic treatment, then freeze-dry the liquid and place the product in a tubular furnace for annealing reaction at 900° C. for 3 hours in an argon atmosphere, and obtain boron-doped graphene after centrifugal washing 4 times in deionized water.
[0047] Step 2: Weigh 0.0273 g of nitrogen-doped graphene, 0.5465 g of polyethylene oxide, and 0.5465 g of lithium bis(trifluoromethanesulfonyl)imide into a conical flask, then add 12 mL of acetonitrile, and stir magnetically for 12 h at room temperature to obtain a uniform PEO casting solution; in addition, prepare a PAN spinning solution according to the method of step 2 of Example 1.
[0048] Step 3: Prepare a PAN porous film according to the method of step 3 of Example 1.
[0049] Step 4: Prepare a boron-doped graphene composite solid electrolyte according to the method of step 4 of Example 1.
[0050] Step 5, testing of ionic conductivity, lithium ion migration number and critical current density of boron-doped graphene composite solid electrolyte and testing of rate performance and cycle stability of lithium iron phosphate | composite solid electrolyte | lithium battery: The assembly and testing methods are the same as step 5 of Example 1. The ionic conductivity of the boron-doped graphene composite solid electrolyte is calculated to be 5.90×10 -5 S cm -2 , the lithium ion migration number is 0.49. The critical current density of the boron-doped graphene composite solid electrolyte is 0.05 mA cm -2 , and the overpotential is 0.15 V. The lithium iron phosphate|composite solid electrolyte|lithium battery assembled with boron-doped graphene composite solid electrolyte has a specific capacity of 148 mAh g at a rate of 0.1C. -1 The specific capacity at 0.5C rate is 92 mAh g -1 , which is about 62% of the 0.1C rate capacity. When cycled at 0.3C rate, the initial capacity is 121 mAh g -1 , and can maintain a cycle of more than 100 circles. Example 4
[0051] This embodiment includes the following steps:
[0052] Step 1. Weigh 250 mg of graphene oxide and 1250 mg of boric acid into a conical flask, then add 50 mL of deionized water, and obtain a uniform liquid after sufficient magnetic stirring and ultrasonic treatment. The liquid is then freeze-dried and the product is placed in a tubular furnace for annealing reaction under argon atmosphere and 800° C. for 3 hours. After centrifugal washing in deionized water for 4 times, boron-doped graphene is obtained.
[0053] Step 2: Take 0.0164 g of boron-doped graphene, 0.5465 g of polyethylene oxide, and 0.3644 g of lithium bis(trifluoromethanesulfonyl)imide into a conical flask, then add 12 mL of acetonitrile, and stir magnetically for 12 h at room temperature to obtain a uniform PEO casting solution; in addition, prepare a PAN spinning solution according to the method of step 2 of Example 1.
[0054] Step 3: Prepare a PAN porous film according to the method of step 3 of Example 1.
[0055] Step 4: Prepare a boron-doped graphene composite solid electrolyte according to the method of step 4 of Example 1.
[0056] Step 5, testing of ionic conductivity, lithium ion migration number and critical current density of boron-doped graphene composite solid electrolyte and testing of rate performance and cycle stability of lithium iron phosphate | composite solid electrolyte | lithium battery: The assembly and testing methods are the same as step 5 of Example 1. The ionic conductivity of the boron-doped graphene composite solid electrolyte is calculated to be 9.36×10 -5S cm -2 , the lithium ion migration number is 0.55. The critical current density of the boron-doped graphene composite solid electrolyte is 0.05 mA cm -2 , and the overpotential is 0.13 V. The lithium iron phosphate|composite solid electrolyte|lithium battery assembled with boron-doped graphene composite solid electrolyte has a specific capacity of 159 mAh g at a rate of 0.1C. -1 , the specific capacity at 0.5C rate is 101mAh g -1 , which is about 64% of the 0.1C rate capacity. When cycled at 0.3C rate, the initial capacity is 138 mAh g -1 , can maintain more than 300 cycles.
[0057] According to the above experiments, the boron-doped graphene composite solid electrolyte provided by the present invention has excellent electrochemical properties and can be widely used in solid-state batteries.
[0058] Compared with the prior art, this method uses boron-doped graphene with electron-deficient centers as filler in solid electrolytes, which is evenly dispersed in the solid electrolyte, reduces the crystallinity of the polymer, promotes the movement of polyethylene oxide segments, and is beneficial to the transmission of lithium ions. In addition, the electron-deficient boron on it can act on negatively charged anions, restraining the movement of anions while promoting the dissociation of lithium salts, releasing more free lithium ions, thereby significantly improving the ionic conductivity and lithium ion migration number of the composite solid electrolyte, thereby giving lithium batteries better rate performance and cycle stability.
[0059] The above-mentioned specific implementation can be partially adjusted in different ways by those skilled in the art without departing from the principle and purpose of the present invention. The protection scope of the present invention shall be based on the claims and shall not be limited by the above-mentioned specific implementation. Each implementation scheme within its scope shall be subject to the constraints of the present invention.
Claims
1. A method for preparing a boron-doped graphene composite solid electrolyte, characterized in that: A mixed solution of polyacrylonitrile (PAN) and N,N-dimethylformamide was prepared into a PAN porous film by electrospinning technology; boron-doped graphene, polyethylene oxide, lithium bis(trifluoromethanesulfonylimide) and acetonitrile were mixed to prepare a PEO casting solution, which was then cast onto the PAN porous film. After vacuum drying, a composite solid electrolyte with polyacrylonitrile fiber as the support, polyethylene oxide as the matrix and boron-doped graphene as the filler was formed.
2. The method for preparing the boron-doped graphene composite solid electrolyte according to claim 1, characterized in that: The boron-doped graphene is prepared by mixing graphene oxide and boric acid and performing annealing reaction.
3. The method for preparing the boron-doped graphene composite solid electrolyte according to claim 1, characterized in that: The amount of the boron-doped graphene is 1%-5% of the mass of polyethylene oxide, and the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to polyethylene oxide is 1:3-1:
1.
4. The method for preparing the boron-doped graphene composite solid electrolyte according to claim 1, characterized in that: The electrospinning method used a syringe to inject the PAN spinning solution into a stainless steel needle, and used aluminum foil as a receiving matrix. The distance between the needle and the receiving matrix was set to 15 cm, and the pushing speed was adjusted to 1 μm s -1 , a voltage of 15 kV was applied for electrospinning.
5. A boron-doped graphene composite solid electrolyte prepared according to the method according to any one of claims 1 to 4, characterized in that: include: Polyacrylonitrile fibers are used as supports for a composite solid electrolyte, polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide are used as a matrix, and boron-doped graphene with electron-deficient boron-containing groups is used as a filler, wherein: the support fibers are interwoven in the composite solid electrolyte to form a three-dimensional skeleton, the matrix forms a continuous lithium ion transport phase in the composite solid electrolyte, and the filler is uniformly dispersed inside the polymer matrix to adsorb anions and reduce the crystallinity of the matrix.
6. An application of a boron-doped graphene composite solid electrolyte prepared according to any one of the methods of claims 1 to 4 or according to claim 5, characterized in that: Assemble them into stainless steel | composite solid electrolyte | stainless steel battery, lithium | composite solid electrolyte | lithium battery and lithium iron phosphate | composite solid electrolyte | lithium battery.
7. The use according to claim 6, characterized in that: The stainless steel|composite solid electrolyte|stainless steel battery is obtained by sequentially placing a composite solid electrolyte and a stainless steel sheet into a battery shell and assembling them; The lithium|composite solid electrolyte|lithium battery is obtained by sequentially placing a lithium sheet, a composite solid electrolyte, and a lithium sheet into a battery shell and assembling them; The lithium iron phosphate|composite solid electrolyte|lithium battery is obtained by sequentially placing a lithium iron phosphate pole piece, a composite solid electrolyte, and a lithium sheet into a battery shell and then assembling them.
Citation Information
Patent Citations
Preparation method of primary electrospinning flexible ultrathin lithium ion battery
CN108054434A
Solid state electrolyte for lithium secondary battery
CN108475808A
Preparation method and application of boron nitride / polyoxyethylene composite solid electrolyte
CN109755645A
PEO-based solid electrolyte as well as preparation method and application thereof
CN113270639A
Solid electrolyte, preparation method thereof and all-solid-state lithium metal battery
CN114552025A